MO520: Prevalence of Anemia in Patients With Stage 3 or 4 Chronic Kidney Disease in Portugal–The Nefropor Study. (3rd May 2022) - Anibal A. Ferreira, Manuel; Aires, Inês; Do Mar Menezes, Maria; Cardoso Fernandes, Sara; Cortesão Costa, Ana; Fernandes, Sara; Farinha, Ana; Furtado, Teresa; Marques, Nídia; Gonçalves, Francisco; Roldão, Marisa; Malho Guedes, Anabela; et al.
Abstract: BACKGROUND AND AIMS: Anemia is a highly prevalent and modifiable comorbidity in patients with chronic kidney disease (CKD), which tends to aggravate as the disease progresses. The economic burden of anemia in CKD is high, and quality of life issues (e.g. fatigue, reduced productivity) is common in these patients. Data on the prevalence and treatment of anemia in CKD stages 3 and 4 (based on the estimated glomerular filtration rate according to KDIGO classification) in Portugal are lacking. The NEFROPOR study aimed to estimate the prevalence of anemia in patients with CKD stage 3 or 4 admitted to a Nephrology consultation between 1 January and 31 March 2017 and characterize anemia treatment in this patient population. METHODS: NEFROPOR was a retrospective, multicentric study carried out in 10 Portuguese centers. All patients aged ≥18 years with stage 3 or 4 CKD admitted to a Nephrology consultation in one of those centers between 1 January and 31 March 2017 were invited to participate, and data for up to 24 months after admission were collected from patients' clinical files. Retrieved data included age, body mass index (BMI), anemia status according to the World Health Organization (WHO) diagnostic criteria, and anemia treatment type and duration. Three assessments of the prevalence anemia were performed: at the time of the first Nephrology visit (presentation), at the first analytical results and the overall prevalence in the study cohort. Statistical analysis was performed in SPSS Statistics (v26) and a 0.05 significance level was adopted. RESULTS: A total of 176 patients were included in this study, mostly (61.9%) male, with a median age of 76 years (range, 26–97) and a mean BMI indicative of pre-obesity (28.2; standard deviation, 4.2). CKD stage 3b was predominant (43.2%), followed by stage 4 (32.4%) and stage 3a (24.4%). The most frequent CKD etiologies in this cohort were diabetes (39.8%), followed by arterial hypertension (27.8%) and unknown cause (25.6%). Arterial hypertension was largely the most frequent comorbidity, present in 90.3% of patients, followed by diabetes (54.0%). Although less prevalent, coronary artery disease (18.2%) and congestive heart failure (14.8%) were also identified in this patient population. A total of 44.9% of patients [95% confidence interval (CI), 37.7%–52.3%] had anemia at presentation, which was significantly associated with CKD stage, diabetes, peripheral vascular disease and myocardial infarction comorbidities, and diabetes and unknown CKD etiology. The overall prevalence of anemia in the study cohort was 61.9% (95% CI 54.6%–68.9%), and it was significantly associated with diabetes and peripheral vascular disease comorbidities and with diabetes and primary glomerulonephritis as CKD etiologies. The prevalence of anemia at the first analytical results was 49.4% (95% CI 42.1%–56.8%), and it was significantly associated with CKD stage, diabetes, non-skin cancer, peripheral vascular disease and myocardial infarction comorbidities, and diabetes as CKD etiology. Figure 1 shows the evolution of anemia treatment in this cohort over 24 + months. CONCLUSION: The three estimates of the prevalence of anemia in this study were consistent with each other, particularly those for the first visit and first analytical results. The latter were also consistent with evidence in the literature reporting a prevalence of anemia in the population of patients with CKD stages 3 and 4 between 40% and 60%. The overall prevalence of anemia in this study was 12%–15% higher than first visit and first analytical results estimates, in agreement with the fact that this refers to a cumulative prevalence. These data support the need for optimized and individualized treatment strategies for patients with CKD stages 3 and 4, maximizing the efficiency of health-care resource use.